2020
DOI: 10.1111/pce.13690
|View full text |Cite
|
Sign up to set email alerts
|

Water and vapor transport in algal‐fungal lichen: Modeling constrained by laboratory experiments, an application forFlavoparmelia caperata

Abstract: Algal‐fungal symbionts share water, nutrients, and gases via an architecture unique to lichens. Because lichen activity is controlled by moisture dynamics, understanding water transport is prerequisite to understand their fundamental biology. We propose a model of water distributions within foliose lichens governed by laws of fluid motion. Our model differentiates between water stored in symbionts, on extracellular surfaces, and in distinct morphological layers. We parameterize our model with hydraulic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Nowadays, lichens have been known to further host prokaryotes, lichenicolous fungi, and viruses (Cardinale et al, 2006;Petrzik et al, 2019;Grimm et al, 2021). A recent study revealed a complete carbon (C) cycling in a lichen symbiotic interaction between algal, fungal, and lichen partners (ten Veldhuis et al, 2020). The mycobiont shapes the thallus structure of lichens that allows better nutrient accessibility, whereas the photobiont (green algae) trades off C in form of sugar and O 2 produced by photosynthesis to other microorganisms in the lichen symbiosis (Pinokiyo et al, 2006;ten Veldhuis et al, 2020;Grimm et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nowadays, lichens have been known to further host prokaryotes, lichenicolous fungi, and viruses (Cardinale et al, 2006;Petrzik et al, 2019;Grimm et al, 2021). A recent study revealed a complete carbon (C) cycling in a lichen symbiotic interaction between algal, fungal, and lichen partners (ten Veldhuis et al, 2020). The mycobiont shapes the thallus structure of lichens that allows better nutrient accessibility, whereas the photobiont (green algae) trades off C in form of sugar and O 2 produced by photosynthesis to other microorganisms in the lichen symbiosis (Pinokiyo et al, 2006;ten Veldhuis et al, 2020;Grimm et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed a complete carbon (C) cycling in a lichen symbiotic interaction between algal, fungal, and lichen partners (ten Veldhuis et al, 2020). The mycobiont shapes the thallus structure of lichens that allows better nutrient accessibility, whereas the photobiont (green algae) trades off C in form of sugar and O 2 produced by photosynthesis to other microorganisms in the lichen symbiosis (Pinokiyo et al, 2006;ten Veldhuis et al, 2020;Grimm et al, 2021). Furthermore, the respiratory CO 2 generated by the mycobiont can also be used by the photobiont (ten Veldhuis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations